Oh yeah, nice and simple. Alright, so we have (f*g)(-4). What this means if that they want you to multiple f(x) by g(x), then plug in -4. Lets go do that
(3x+5)(-4x+7)
-12x^2+21x-20x+35
-12x^2+x+35
So, that is what (f*g)(x) is. Now, lets plug in -4
-12(-4)^2+(-4)+35
-12(16)-4+35
-192-4+35
-161
So, your answer would be -161
THIS IS THE EASY WAY!
So, the easy way is to plug in -4 into both f(x) and g(x), them ultiple the solution of each by each other. So,
f(-4)=3(-4)+5 g(-4)=-4(-4)+7
f(-4)=-12+5 g(-4)=16+7
f(-4)=-7 g(-4)=23
When you multiple -7 * 23, you would get the same answer: -161